Experimental investigation on the performance of bone glue and crumb rubber compound modified asphalt. (25th October 2021) - Lv, Songtao; Tan, Li; Peng, Xinghai; Hu, Long; Borges Cabrera, Milkos
Highlights: A new sustainable asphalt material was developed. BG/CR compound modified asphalt has satisfactory physical and rheological properties. Bone glue improved the compatibility between crumb rubber and asphalt. Abstract: Bone glue (BG) and crumb rubber (CR), as waste derivatives, have the advantages of low cost, green, and extensive sources. At present, the research and application of BG in road engineering are still insufficient, and there are few studies on using the combination of BG and CR for asphalt modification. Thus, this work studied the effect of BG and CR composite modification on the performance of asphalt. A series of conventional tests and rheological tests, including penetration, softening point, phase separation, temperature sweep (TS), multiple stress creep and recovery (MSCR), were used to evaluate high-temperature properties. Bending beam rheological (BBR) test and ductility test were carried out to assess the low-temperature characteristics of composite modified asphalt. Finally, the microstructure of composite modified asphalt was studied by fluorescence microscope (FM). The functional groups referring to the chemical components present of BG/CR composite modified asphalt were identified through Fourier transform infrared (FTIR) spectroscopy. It can be found from the results that the penetration decreases, and the softening point and ductility increase. Moreover, the combination of BG and CR increases the rutting factor, recovery rate, and creep rate. Besides, this composite material decreases the creep modulus and non-recoverable creep compliance. Furthermore, it was found that blending BG and CR into asphalt can enhance its high- and low-temperature characteristics. In addition, BG significantly enhances the CR-modified asphalt's storage stability, and the BG/CR modifier is uniformly and stably dispersed in the matrix asphalt. FT-IR results showed that the composite modification between BG, CR, and asphalt matrix is a physical process.